From effluent to algal bloom: linking wastewater infrastructure, nutrient enrichment, and ecosystem stress in the Arabian Gulf - Gastoldi, Lucia; Al Gergawi, Amal; Burt, John A. (Frontiers in Water, 2025)
Municipal wastewater discharge has emerged as the dominant driver of coastal eutrophication in the Arabian/Persian Gulf, distinguishing the region from most marine basins where agricultural runoff prevails. This paper synthesizes data on nutrient loads, eutrophication symptoms and wastewater governance across the eight Gulf nations, drawing on a combination of national reporting, published literature, and long-term coastal monitoring records. The findings reveal that untreated or insufficiently treated municipal effluents contribute the majority of anthropogenic nitrogen and phosphorus input to Gulf waters, with agricultural sources playing only a minor role. Symptoms of eutrophication, such as harmful algal blooms, hypoxia and ecosystem degradation, have become increasingly frequent and spatially widespread. These impacts are particularly pronounced in semi-enclosed, poorly flushed lagoons and bays common to many parts of the Gulf, where anthropogenic nutrient enrichment coincides with elevated biological and physical vulnerability. Despite these trends, regulatory standards for wastewater treatment remain inconsistent across the region, and infrastructure upgrades have not kept pace with population growth and urban expansion. Addressing wastewater-driven eutrophication in the Gulf will require a coordinated regional response that includes harmonized effluent standards, strategic investment in tertiary treatment, and improved monitoring and data sharing. By identifying key knowledge gaps and management priorities, this paper provides a regional framework to support evidence-based policymaking and reduce the long-term ecological and socio-economic consequences of coastal nutrient enrichment.